Profitability of Cedrela odorata L. in Agroforestry Systems with Coffee in Pérez Zeledón, Costa Rica - González-Rojas, Mariela (2017)
The objective of this research was to determine the production of cedar wood in agroforestry systems (AF) with coffee, using a prediction model of the commercial volume obtained in the study area, as well as the profitability generated by the sale of coffee, wood and payment for environmental services (PPSA). The study was carried out in the canton of Pérez Zeledón, province of San José, Costa Rica. There were established 30 temporary sampling plots of 1000 m2 in AF with cedar between five and 17 years of age. The diameter growth (DBH) and the commercial height (CH) of the species were evaluated, as well as the management of the SAF (activities, inputs and yields) and coffee production through the producer interview. The obtained models allowed to predict the commercial volume (m3 tree-1) according to age (R2 = 88.7%), DBH (R2 = 90.3%) and CH (R2 = 97.2%). The average coffee production of the sampled sites was 26 fanegas ha-1 year-1. At the age of 17 years of the cedar, a production of 1.04 m3 tree-1 (92.13 m3 ha-1) of standing timber was obtained, which represented a financial contribution of 81% of the net present value (NPV) of the AF in the analysis period. The estimated financial indicators allow concluding that the coffee-cedar AF is profitable since it generated a positive NPV of ₡ 8 198 601,5, an internal rate of return (IRR) of 16% which was higher than the cost of money (discount rate of 6.1%) and a B/C ratio of 1.34.